Effects of intercropping desho grass (Pennisetum glaucifolium) with vetch (Vicia villosa) on soil fertility, forage accumulation, and nutritional composition - Berhanu, M.; Salo, S.; Bezabih, Melkamu; Guyo, M. (Wiley, 2026)
Enhancing feed resource availability and nutritional qualities with healthful soil management practices is a decisive intervention for future livestock husbandry in developing countries. However, there is a need for sound recommendations on agronomic practices and fertilization due to local differences in the climate and soil profiles. Therefore, this study evaluated the intercropping effects of desho grass (Pennisetum glaucifolium) with vetch (Vicia villosa) variety of Var-Lalisa on soil fertility, forage accumulation (FA), and nutritional compositions among seeding rates across harvest days. The experiment was conducted in a randomized complete block design for intercropping of the desho grass with vetch at the seeding rates of 12 kg/ha (T1), 9 kg/ha (T2), 6 kg/ha (T3), 0 kg/ha or sole desho grass (T4), and sole vetch (30 kg/ha) (T5) with three replications. Data on soil profile in depths, plant height, biological compatibility and yield advantage, FA by forage type, and chemical compositions were studied across harvesting. The intercropping effect was substantially greater (p < 0.05) on plant height and FA than sole sown desho grass at all harvests. Moreover, T1 had the highest total forage accumulation (TFA), crude protein (CP), and in vitro organic matter digestibility (IVOMD). However, lower CP and IVOMD were obtained in T4 across the harvests. The sole desho grass yields significantly (p < 0.05) higher ash, acid detergent fiber, neutral detergent fiber, and acid detergent lignin contents. Therefore, the intercropping effect of T1 at higher sowing rates of vetch can maximize the TFA and soil nutrient utilization efficiency, and this can be suggested for further accession study in a range of agroecologies for adoption.